2011
DOI: 10.1016/s1474-4422(10)70300-8
|View full text |Cite
|
Sign up to set email alerts
|

Very early hypothermia induction in patients with severe brain injury (the National Acute Brain Injury Study: Hypothermia II): a randomised trial

Abstract: Summary Background The inconsistent effect of hypothermia treatment on severe brain injury in previous trials might be because hypothermia was induced too late after injury. We aimed to assess whether very early induction of hypothermia improves outcome in patients with severe brain injury. Methods The National Acute Brain Injury Study: Hypothermia II (NABIS: H II) was a randomised, multicentre clinical trial of patients with severe brain injury who were enrolled within 2·5 h of injury at six sites in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
312
2
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(333 citation statements)
references
References 26 publications
4
312
2
8
Order By: Relevance
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 91%
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 91%
“…One might argue that a delayed initiation of hypothermia after injury might be contributory to the negative findings. However, as has been shown most recently, even the application of very early hypothermia after severe TBI (within 2.5 h after injury) did not confirm the usefulness of hypothermia as a primary neuroprotective treatment [109].…”
Section: Tbimentioning
confidence: 76%
“…The review found that the greatest benefit occurred when hypothermia was maintained for 48 hours; however hypothermia doubled the risk of pneumonia [60]. In 2011 the National Acute Brain Injury Study: Hypothermia II was published after being terminated early for futility [61]. No benefit could be attributed to early induced hypothermia in trauma patients [61].…”
Section: Traumamentioning
confidence: 99%
“…In 2011 the National Acute Brain Injury Study: Hypothermia II was published after being terminated early for futility [61]. No benefit could be attributed to early induced hypothermia in trauma patients [61]. However, the group containing intentionally hypothermic patients had a higher daily 20,36 Possible hemodilution 83 Possible coagulation derangements 83 …”
Section: Traumamentioning
confidence: 99%